2021
DOI: 10.3390/w13091233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Agricultural Water Savings–Economy–Ecological Environment System in an Arid Area of Northwest China Using a Water Rights Transaction Model

Abstract: As water trading has become increasingly used to optimize the allocation of water resources, it has become necessary to transfer agricultural water allocations for economic development and ecological environmental uses by way of water rights trading. In this paper, we constructed an example water rights trading model in the arid oasis area of Shihezi Irrigation District (located in Northwest China), using the field investigation method and governmental water management decisions based on the systems theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Water rights trading is one of the important means of water resource management, and many studies have confirmed that implementing a tradable water rights system can improve the efficiency of water resource allocation [22][23][24][25]. With the gradual improvement of the theoretical system of water rights and the vigorous development of the water market, scholars have studied the water rights trading model in order to further improve the utilization rate of regional water resources and optimize its redistribution [26][27][28]. However, most of the studies are mostly on the same level to optimize the objectives for decision-making, without considering the relationship between different levels in an integrated manner, such as the influence of interactive decision-making between regional management and water-use units, and there are few studies on the water rights trading model under the multi-layer perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Water rights trading is one of the important means of water resource management, and many studies have confirmed that implementing a tradable water rights system can improve the efficiency of water resource allocation [22][23][24][25]. With the gradual improvement of the theoretical system of water rights and the vigorous development of the water market, scholars have studied the water rights trading model in order to further improve the utilization rate of regional water resources and optimize its redistribution [26][27][28]. However, most of the studies are mostly on the same level to optimize the objectives for decision-making, without considering the relationship between different levels in an integrated manner, such as the influence of interactive decision-making between regional management and water-use units, and there are few studies on the water rights trading model under the multi-layer perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Dionisio et al (2020) indicated that cross-basin water rights trading may damage the environmental flow and affect water use in the downstream basin, where the water is sold; this may not be conducive to sustainable economic growth. He et al (2021) constructed a water rights trading model based on the systems theory of the agricultural water savings-economy-ecological environment, and analyzed the industrial impact produced by water trading. Although these qualitative studies have determined various ecological problems, they ignored the economic and social aspects, and did not portray a systematic understanding of the compensation system.…”
Section: Introductionmentioning
confidence: 99%
“…Since the establishment of the most stringent water management system in 2011, China has achieved the sustainable utilization of water resources, and increasing numbers of studies have evaluated the effects of this system on water resources management (Shang et al, 2017;He et al, 2021). For example, Guo & Wang (2021) established a prediction model to evaluate the carrying capacity of water resources in China in 2030 under this water resources management system.…”
Section: Introductionmentioning
confidence: 99%